English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

Please help with this equation is needed A.S.A.P!

2006-11-05 06:26:14 · 5 answers · asked by Brainman 2 in Science & Mathematics Mathematics

5 answers

first multiple everythingby x, then simplify and solve:

1/x-2 = 3/x+3 =>

x/x - 2x = 3x/x +3x =>

1 - 2x = 3 + 3x =>

-2 = x

2006-11-05 06:33:13 · answer #1 · answered by Gary H 6 · 0 0

Given: a = (a million / x) and b = (a million / y) Given equipment of equations: (a million / x) + (3 / y) = (3 / 4) (3 / x) - (2 / y) = (5 / 12) Step a million: Convert the 1st equation to a minimum of one utilising a and b variables. inspect the variables on the left hand area. (a million / x) = a (3 / y) = 3 * (a million / y) = 3 * b = 3b consequently: (a million / x) + (3 / y) = 3 / 4 a + 3b = (3 / 4) Step 2: Convert the 2d equation to a minimum of one utilising a and b variables. inspect the variables on the left hand area. (3 / x) = 3 * (a million / x) = 3 * a = 3a (2 / y) = 2 * (a million / y) = 2 * b = 2b consequently: (3 / x) - (2 / y) = (5 / 12) 3a - 2b = (5 / 12) Your converted equipment of equations is: a + 3b = (3 / 4) 3a - 2b = (5 / 12) Step 3: Multiply the 1st converted equation by skill of -3. -3(a + 3b) = -3(3 / 4) -3(a) - 3(3b) = (-9 / 4) -3a - 9b = (-9 /4) Your equipment of equations is now: -3a - 9b = (-9 /4) 3a - 2b = (5 / 12) Step 4: upload them mutually to do away with the a words. -3a - 9b = (-9 /4) 3a - 2b = (5 / 12) -------------------------- -11b = (-9 / 4) + (5 / 12) Step 5: The liquid crystal demonstrate on the RHS is 12. Multiply (-9 / 4) * (3 / 3) to get the liquid crystal demonstrate for the fractions on the RHS. -11b = (-9 / 4)(3 / 3) + (5 / 12) -11b = (-27 / 12) + (5 / 12) Step 6: Now that the denominators are an identical, you could combine the fractions on the RHS. -11b = (-27 + 5) / 12 -11b = (-22 / 12) Step 7: Divide the two components by skill of -11. -11b / -11 = (-22 / 12) / -11 b = (2 / 12) b = (a million / 6) Step 8: Plug this lower back into between the equations to discover a. a + 3(a million / 6) = (3 / 4) a + (a million / 2) = (3 / 4) Subtract (a million / 2) from the two components. a = (3 / 4) - (a million / 2) Step 9: The liquid crystal demonstrate on the RHS is 4. Multiply (a million / 2) * (2 / 2) to get the liquid crystal demonstrate for the fractions on the RHS. a = (3 / 4) - (a million / 2)(2 / 2) a = (3 / 4) - (2 / 4) a = (a million / 4) Step 10: resolve for x and y. Plug those into the given variables. a = (a million / x) (a million / 4) = (a million / x) circulate-multiply. a million * x = a million * 4 x = 4 Plug those into the given variables. b = (a million / y) (a million / 6) = (a million / y) circulate-multiply. a million * y = a million * 6 y = 6 answer: (4, 6)

2016-11-27 20:25:33 · answer #2 · answered by magoon 4 · 0 0

x≠2 or -3

Cross multiply:
1(x+3)=3(x-2)

Distributive property:
x+3=3x-6

Subtract 3x on both sides:
-2x+3=-6

Subtract 3 on both sides:
-2x=-9

Divide -2 on both sides:
x=9/2 or 4.5

Check:
1/(9/2-2)=3/(9/2+3)
1/(9/2-4/2)=3/(9/2+6/2)
1/(5/2)=3/(15/2)
2/5=(3*2)/15
2/5=6/15
2/5=2/5

I hope this helps!

2006-11-05 09:09:05 · answer #3 · answered by Anonymous · 0 0

1/x = 3/x + 5
so 1/x - 3/x = 5
so -2/x = 5
so x = -2/5

2006-11-05 06:30:19 · answer #4 · answered by ? 7 · 0 0

1/(x-2)=3/(x+3)
x+3=3x-6
9=2x
x=4.5

2006-11-05 06:36:16 · answer #5 · answered by Biu3 1 · 1 0

fedest.com, questions and answers